Research Mapping of Working Capital Turnover (WCT) Ratio in Islamic and Conventional Banking: Vosviewer Bibliometric Study and Literature Review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria (Global Financial Accounting Journal, 2023)
Purpose - This study aims to determine the research mapping regarding the Working Capital Turnover (WCT) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Research Method – Data analysis techniques include: (1) mapping the distribution of journal publications around the WCT ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the WCT ratio based on the number of clusters and their items; and (3) mapping research topics around the WCT ratio using a literature review study. Findings – The results showed that: (1) based on the distribution of journal publications, there were 89 journal publications regarding the WCT ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the WCT ratio are divided into 6 clusters and 130 topic items; (3) based on the mapping of literature review studies, there are 19 topics around the WCT ratio. Implication - The implications and contributions of this research are to map research topics around WCT ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.